At the coalface–medical ethics in practice. Futility and death in paediatric medical intensive care. Issue 5 (October 1996) - Balfour-Lynn, I M; Tasker, R C
Abstract : We have conducted a retrospective study of deaths on a paediatric medical intensive care unit over a two-year period and reviewed similar series from outside the UK. There were 89 deaths out of 651 admission (13.7% mortality). In almost two-thirds of the cases death occurred with a decision to limit medical treatment or withdraw mechanical ventilation, implying that additional or further therapy was considered futile. We highlight this as a crucially important issue in the practice of intensive care. More comprehensive studies are needed to help clinicians derive consensus on what constitutes a futile intervention, and therefore when such an intervention should be withheld. This will help families and society better understand the limitations of intensive care.